Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Ular Tangga Kelas VII SMPN Satap Kaili di Suli Barat Luwu - Alamsyah, Muhammad Fauzi; Firman, Firman; Yamin, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan, 2025)
This study discusses development of Islamic Religious Education Learning Media Based on Snakes and Ladders for Class VII of SMPN Satap Kaili in West Suli, Luwu. The objectives of this research are: 1) to identify the development stages of the learning media, 2) to evaluate the validity test results of the learning media, and 3) to examine the practicality test results of the Development of Islamic Religious Education Learning Media Based on Snakes and Ladders for Class VII of SMPN Satap Kaili in West Suli, Luwu. This research is a study using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SMPN Satap Kaili. The research subjects were 17 seventh-grade students at SMPN Satap Kaili. Data collection techniques included observation, interviews, and questionnaires. The collected data were analyzed using data analysis techniques. The results of data analysis show that: 1) the development stages of the Islamic Religious Education learning media based on the Snakes and Ladders game for Grade VII at SMPN Satap Kaili followed the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation; 2) the validity of the learning media, based on expert assessments, reached 86% from media experts, 96% from subject matter experts, and 69% from language experts; 3) the average media validation score was 83.67%, and the average practicality score of the learning media was 91%. Based on these results, it can be concluded that the development of Islamic Religious Education Learning Media Based on Snakes and Ladders for Class VII of SMPN Satap Kaili in West Suli, Luwu.